2020
DOI: 10.30651/jkm.v0i0.5658
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pendidikan Kesehatan Dengan Metode Ceramah Dan Audiovisual Terhadap Pengetahuan Tentang Infeksi Menular Seksual Pada Remaja

Abstract: ABSTRAK Keywords:Health education, lecture methods, audiovisual media, sexually transmitted infectionsObjective: To determine the effect of health education with lecture methods and audiovisual media on knowledge of sexually transmitted infections in adolescentsMethod:This article is a quantitative study using a quasy experimental design with a randomized pretest-posttest two group design approach with 94 respondents divided by 2. Data were analyzed by paired sample T test.Results: The results of the average p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
1
6
0
8
Order By: Relevance
“…This study and other studies have consistently shown that health education using a lecture could improve respondents' knowledge 21 . The purpose of health education is to achieve changes in the behavior of individuals, families and communities in fostering and maintaining healthy behavior and a healthy environment, and to play an active role in bringing about optimum degrees of health 21 .…”
Section: Respondents' Knowledge Difference Before and After Interventionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study and other studies have consistently shown that health education using a lecture could improve respondents' knowledge 21 . The purpose of health education is to achieve changes in the behavior of individuals, families and communities in fostering and maintaining healthy behavior and a healthy environment, and to play an active role in bringing about optimum degrees of health 21 .…”
Section: Respondents' Knowledge Difference Before and After Interventionsupporting
confidence: 79%
“…Health education is one of the efforts to increase knowledge in communities 20 . Health education can be done in various media, including audiovisual media 21 . Such health education can be done by various methods, including the lecture method, information obtained by the method.…”
Section: Respondents' Knowledge Difference Before and After Interventionmentioning
confidence: 99%
“…Penderita Infeksi menular seksual di Indonesia terutama di kota-kota besar seperti Jakarta, Bandung, Jogjakarta, Surabaya sebagian besar diderita oleh remaja umur14-18 tahun sebanyak 32% bahkan satu dari empat remaja sudah melakukan hubungan seksual. 62,7% remaja perempuan kehilangan keperawanan dan sudah melakukan praktik abortus (Ramadhani & Ramadani, 2020). Setiap tahunnya sekitar 70.000 terjadi kematian pada remaja karena melakukan aborsi dan menyumbang tingginya angka HIV/AIDS serta kematian ibu (Triyanto dkk., 2021).…”
Section: Pendahuluanunclassified
“…Education can be done in various ways, such as through guidance and counseling, small groups such as brainstorming, snowballing, roleplay, and small discussion groups, and also large groups such as lectures and seminars (Purwasi, 2021). According to Rahmawati & Elsanti, 2020, in their research which aimed to assess the effectiveness of the lecture and SGD method on reproductive health on the level of knowledge and attitude of teenagers, it was explained that the SGD method was effective for increasing knowledge. This is in line with research entitled "The Effect of Health Education Using the SGD Method on Behavior to Prevent HIV/AIDS Transmission", where significant results were obtained (p) 0.000, which means health education using the SGD method is effective in improving knowledge about HIV/AIDS prevention (Choudhary et al, 2020).…”
Section: Introductionmentioning
confidence: 99%